Optimasi micro frontend website untuk meningkatkan load times: teknik, tantangan, dan best practice - Aldy Akbarrizky; Bambang Wisnuadhi; Lukmannul Hakim Firdaus; [1] S. Peltonen, L. Mezzalira, and D. Taibi, “Motivations, benefits, and issues for adopting Micro-F (Computer Science and Information Technology, 2023)
In recent years, there has been an increasing popularity of the micro frontend architecture due to its implementation by large companies such as IKEA, Starbucks, and Amazon. Due to its characteristics that similar to microservices, this architecture started to be implemented by various companies to improve their developer experience. However, this architecture has some issues, one of which is the performance of page load time. The objective of this research is to find and determine the best practices for optimizing the page load time of micro frontend applications and to identify the challenge involved. The research is conducted by implementing optimization techniques such as code splitting, lazy loading, tree shaking, minification, and utility modules to micro frontend website. After that, the website is tested with a sample size of 200 which determined by using Lemeshow formula. The research is conducted in both local and server environments using the Google Chrome browser and used "fully loaded" metric. The research use a simple Enterprise Resource Planning (ERP) application consisting of five micro frontends built with React, Vue, and Angular frameworks. The experimental results show that implementing all of the optimization techniques on all micro frontends can improve the application's page load time performance by 31.79% in the local and 47.5% in the server environment.